α + t three-body reactions and excited levels of the lightest nuclei - O. K. Gorpinich; O. M. Povoroznyk (Ядерна фізика та енергетика)
The three-body reactions from interaction alpha-particle with energy 67.2 MeV and tritium were investigated in kinemanically-complete experiment. The excitation energies and energy widths of some unbound levels of nuclei 4 H, 5 Не and 6 Li were determined using of sequential decay model.